INTEGRATING MEASLES, MUMPS, AND RUBELLA BIOLOGICAL - Pushpa Pandey (International Journal of Multidisciplinary Research and Studies, 2021)
As the pandemic proceeds, it is possible that the provision of scientific data indicating that live attenuated vaccines have the capacity to prevent infection and/or minimise the severity of COVID-19 might have an influence on the regulations that govern public health. It is crucial, therefore, to determine whether or whether a live attenuated vaccine might be utilised to protect against infection with SARS-CoV-2 and hospitalisation for COVID-19, especially in children. Since 2018, the percentage of people in France receiving the MMR vaccination has gone up. By examining the impact of the live attenuated MMR vaccination on the risk of being hospitalised for COVID-19 in children using the countrywide French National Health Data System, we tested the hypothesis that this vaccine provides non-specific main protection against COVID-19 (SNDS).